Some Results on the Generalized Cayley Graph of Complete Graphs - Neamah, Suad Abdulaali; Erfanian, Ahmad (Iraqi Journal of Science, 2023)
. Suppose that is the Cayley graph whose vertices are all elements of and two vertices and are adjacent if and only if . In this paper,we introduce the generalized Cayley graph denoted by which is a graph with a vertex set consisting of all column matrices in which all components are in and two vertices and are adjacent if and only if , where is a column matrix that each entry is the inverse of the similar entry of and is matrix with all entries in , is the transpose of and and m . We aim to provide some basic properties of the new graph and determine the structure of when is a complete graph for every , and n, m .